Potential human health risk assessment associated with Hg, Cd, Pb, and As in sardines and shrimp from four Egyptian coastal governorates - Mohamed A. Embaby; Ahmed M. Ayesh; Salah H. Salem; Gomaa N. Abdel-Rahman (Toxicology Reports)
Heavy metal contamination in seafood is a developing concern due to the potential negative consequences on human health. Egypt's coastal regions are important for seafood production and consumption, making it critical to assess the safety of these aquatic resources. The current study examined toxic metal levels (Hg, Pb, Cd, and AS) in 96 samples of sardine and shrimp from four Egyptian coastal governorates (Alexandria, Kafr El-Sheikh, Damietta, and Port Said) from 2019 to 2021. Inductively coupled plasma-optical emission spectroscopy (ICP-OES) was used to investigate the four hazardous metals. The recovery percentages of the determined metals ranged between 97 % and 99 %. Limits of detection (LOD) and limit of quantification (LOQ) for the determined metals ranged from 0.001 to 0.0077 mg/l and from 0.0035 to 0.026 mg/l, respectively. Mercury (Hg) was not found in any of the samples tested. The concentrations of Pb and Cd in the sardines and shrimp samples were higher in the winter seasons than in the summer seasons. Meanwhile, the difference in seasons had no effect on the concentration of As in the sardines and shrimp samples. The highest concentrations of the other three metals in the sardine and shrimp samples were used to calculate the Estimated Daily Intake (EDI), Target Hazard Quotient (THQ), and Hazard Index (HI). The obtained THQ as well as the HI of Pb, Cd, and As were all less than 1.0 (with the exception of sardine samples from Kafr El-Sheikh Governorate, which recorded 1.262), indicating that there is no significant health risk to the consumer from consuming such sardines and shrimp from these governorates. The effect of different seasons on the concentrations of the metals under study does not have a specific behavior, but varies according to the governorate, the type of sample, and the type of contaminated metal. Due to the high level of contamination with heavy metals in sardine samples collected from Kafr El-Sheikh governorate (TTHQ = 1.26), an environmental study is required to determine the causes of contamination and control them.